Tradução, adaptação cultural e análise das propriedades de medida da measure of processes of care-20 e measure of processes of care-sp para a língua portuguesa Brasil - Ana Amelia Moraes Antunes (2018)
The MPOC questionnaires evaluate Family-Centered Practice (PCP) in services for children with movement disorders or with chronic health conditions that affect their development during childhood. The MPOC contains the MPOC-20 and MPOC-SP designed to be completed by parents/guardians and by rehabilitation professionals, respectively. These questionnaires are widely used in the literature for the evaluation of family-centered approaches. Objectives: To translate and culturally adapt the MPOC-20 and MPOC-SP to Portuguese-Brazilian language and to evaluate its psychometric properties. Methodology: This is a methodological study accomplished with the following stages: translation and back-translation performed by a committee of experts; cognitive interviews with the preliminary versions, testing the pre-final versions and evaluating the psychometric properties of the translated versions. The study was carried out in four capitals cities in Brazil in view of our territorial extension and cultural diversity. Results: Cognitive interviews were conducted in rounds solving the participants' doubts regarding the questions, and the pre-testing ensured the comprehension of the translated versions. The MPOC-20 internal consistency varied (n = 107) between 0.61 and 0.91, the test-retest reliability (n = 50) between 0.44 and 0.83 and the standard error of measurement between 0.66 and 0.85. The MPOC-SP internal consistency varied (n = 92) between 0.523 and 0.835, the test-retest reliability (n = 62) between 0.83 and 0.90 and the standard error of measure between 0.34 and 0, 46. Conclusion: The Brazilian versions of the MPOC-20 and the MPOC-SP are stable and reliable. These instruments are relevant to the evaluation of FCP in health services and provide information that could modify the services ensuring better care.